A hundred summers [large type] - Williams, Beatriz (Thorndike Press, 2013)
Memorial Day, 1938: New York socialite Lily Dane has just returned with her family to the idyllic oceanfront community of Seaview, Rhode Island, expecting another placid summer season among the familiar traditions and friendships that sustained her after heartbreak. That is, until the Greenwalds take up residence in Seaview. Nick and Budgie Greenwald are an unwelcome specter from Lily's past: her former best friend and her former fiancé, now recently married -- an event that set off a wildfire of gossip among the elite of Seaview, who have summered together for generations. But the ties that bind Lily to Nick are too strong and intricate to ignore, and the two are drawn back into long-buried dreams, despite their uneasy secrets and many emotional obligations. Under the scorching summer sun, the unexpected truth of Budgie and Nick's marriage bubbles to the surface, and as a cataclysmic hurricane barrels unseen up the Atlantic and into New England, Lily and Nick must confront an emotional cyclone of their own, which will change their worlds forever.